High‐density mapping to guide ablation of a right bundle branch morphology premature ventricular contraction from the right outflow tract. Issue 6 (16th April 2018) - De Simone, Antonio; La Rocca, Vincenzo; Panella, Alfonso; Bianchi, Valter; Maddaluno, Francesco; Stabile, Giuseppe; Garcia Bolao, Ignacio
Key Clinical Message: The Rhythmia ultrahigh‐density mapping system with a specific algorithm seems to be helpful in identifying the target area to successfully treat multiple morphologies by catheter ablation in the right ventricular outflow tract RVOT. Interestingly, the acquisition process seemed to be extremely faster than a standard manual point‐by‐point premature ventricular contraction (PVC) mapping. Abstract : The Rhythmia ultrahigh‐density mapping system with a specific algorithm seems to be helpful in identifying the target area to successfully treat multiple morphologies by catheter ablation in the RVOT. Interestingly, the acquisition process seemed to be extremely faster than a standard manual point‐by‐point premature ventricular contraction (PVC) mapping.